Sustainability of bio-mediated and bio-inspired ground improvement techniques for geologic hazard mitigation: a systematic literature review - Faruqi, Aisha; Hall, Caitlyn A.; Kendall, Alissa (Frontiers in Earth Science, 2023)
This is a systematic literature review of quantitative sustainability assessments, focusing on life cycle sustainability assessment (LCSA), of bio-mediated and bio-inspired ground improvement technologies applied to geologic hazard mitigation. The aims of the systematic review are to (1) compare the sustainability of various ground improvement techniques and, (2) to evaluate the rigor and consistency of sustainability assessment methods applied to these techniques. The literature review considers studies identified through keyword searches of bibliographic databases. After selection criteria were applied to ensure identified articles were within scope, a total of 8 articles were found which assessed bio-mediated and bio-inspired ground improvement technologies. The technologies represented in the literature include enzyme induced carbonate precipitation (EICP), microbially induced carbonate precipitation (MICP), and microbially induced desaturation and carbonate precipitation (MIDP). While sustainability is typically conceived to include environmental, economic and social impacts, most studies examined only life cycle environmental impacts, three included life cycle cost accounting, and none included social impacts. Analysis of the studies' system boundaries show inconsistencies across studies, making comparison of results inaccurate. The most common environmental impact categories included in the identified studies are global warming and eutrophication. Raw materials production and field emissions from the biogeochemical reactions that drive the technologies are the largest contributors to these impacts. Based on the review, it is clear that a set of LCSA guidelines is needed to produce high-quality LCSAs that can be used in comparative assessments and to confidently identify processes where the impacts of bio-mediated and bioinspired technologies can be reduced.